Academic support required by university students: evidence for higher education academic support policies - Valenzuela, Jorge; Miranda-Ossandón, Jorge; Gonzalez Sanzana, Alvaro; Muñoz, Carla (My University, 2021)
This primary aim of this study is to characterize the different types of academic support that university students require to successfully complete their studies. The context is a growing demand for inclusive access to higher education. The sample is composed of 758 Chilean university students. The types of support that students perceive as essential are identified hierarchically and their diversity is examined. The results show high demand for all the academic support types assessed. This puts into question the approach used by educational institutions, which focuses on specific aspects identified as deficiencies, and suggest that academic support-related issues should be understood and addressed from a broader, more holistic, and more integrated manner. It is concluded that strategic and instrumental academic supports are the main academic supports required by students.
Keywords: academic assistance; academic support; higher education; university services; university students